Cancer as a channelopathy: ion channels and pumps in tumor development and progression - Litan, Alisa; Langhans, Sigrid A. (Frontiers in Cellular Neuroscience, 2015)
Increasing evidence suggests that ion channels and pumps not only regulate membrane potential, ion homeostasis, and electric signaling in excitable cells but also play important roles in cell proliferation, migration, apoptosis and differentiation. Consistent with a role in cell signaling, channel proteins and ion pumps can form macromolecular complexes with growth factors, and cell adhesion and other signaling molecules. And while cancer is still not being cataloged as a channelopathy, as the non-traditional roles of ion pumps and channels are being recognized, it is increasingly being suggested that ion channels and ion pumps contribute to cancer progression. Cancer cell migration requires the regulation of adhesion complexes between migrating cells and surrounding extracellular matrix (ECM) proteins. Cell movement along solid surfaces requires a sequence of cell protrusions and retractions that mainly depend on regulation of the actin cytoskeleton along with contribution of microtubules and molecular motor proteins such as mysoin. This process is triggered and modulated by a combination of environmental signals, which are sensed and integrated by membrane receptors, including integrins and cadherins. Membrane receptors transduce these signals into downstream signaling pathways, often involving the Rho GTPase protein family. These pathways regulate the cytoskeletal rearrangements necessary for proper timing of adhesion, contraction and detachment of cells in order to find their way through extracellular spaces. Migration and adhesion involve continuous modulation of cell motility, shape and volume, in which ion channels and pumps play major roles. Research on cancer cells suggests that certain ion channels may be involved in aberrant tumor growth and channel inhibitors often lead to growth arrest. This review will describe recent research into the role of ion pumps and ion channels in cell migration and adhesion, and how they may contribute to tumor development.